MP3-music player application development - Tan, Jia Yi (2022)
This project is an MP3 Music Player design project for academic purpose. It will provide the methodology, concept and design of a music player. This project is about developing an MP3 music player application for Android. The most significant distinction between the music player and other MP3 application is that it is absolutely free to use. It will incorporate the benefits of existing music players on the market, mining out as many functions as possible from existing music players, and then filtering to exclude functions that are not practical or pricy. It will also be enhanced depending on user comments. Audio is a crucial mode of communication, equally as significant as text nowadays. As we all know that the audio files are digital data, so we’ll need a tool to execute the digital files, or to play the files. We can never listen to music, movies, or the contents of an audio file without this tool or player. As a result, we require music players. This gadget allows us to listen to music and other digital audio files. We can accomplish that without downloading and installing paid music players. The music player GUI project concept attempts to simulate a physical music player. This software enables us to listen to songs, music, and all music files on our mobile phone. The music player application must be capable of playing a song, creating, and displaying a playlist, pausing and restarting a long song, changing the song, and play the previous or subsequent song. The agile development cycle was employed to create the mp3 music application for this project. The agile development cycle contained six phases which is requirements elicitation, planning, design, development and implementation, testing, and deployment. Because of the iterative and flexible character of this technique, it can efficiently adapt to changing user requirements.